Polyester Recycled Film
By optimizing the viscosity ranges and intrinsic viscosity values of polyester films, the issue of thickness unevenness is addressed, resulting in high-quality films with improved uniformity and the potential for recycled material usage.
Patent Information
- Application Number
- JP2024109986
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2024-06-17
- Filing Date
- 2024-07-09
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-07-09
AI Technical Summary
Polyester films with added plasticizers often experience thickness unevenness, which is a challenge in achieving high-quality films with precise thickness control.
The development of a polyester film with specific viscosity ranges and intrinsic viscosity values, combined with a formula that ensures shear viscosity and intrinsic viscosity are within optimal limits, thereby minimizing thickness unevenness.
This approach results in polyester films with extremely small thickness unevenness and the ability to incorporate recycled raw materials, enhancing both quality and sustainability.
Smart Images

Figure 0007666716000001 
Figure 0007666716000002 
Figure 0007666716000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyester film which is characterized by low shear viscosity without significantly impairing the intrinsic viscosity and has good thickness uniformity. [Background technology]
[0002] Polyester films have excellent mechanical properties, thermal properties, chemical resistance, electrical properties, and moldability, and are used in a variety of applications. Among polyesters, polyethylene terephthalate (PET) in particular has excellent transparency and processability, and is therefore widely used in applications that require high quality, such as optical films and release films. Among the quality factors, thickness accuracy requires strict management, as it affects color unevenness in optical films and affects unevenness in lamination thickness when an object to be released is placed on top of the film in release films.
[0003] A melt film-forming method is known as a method for producing polyester films, and the shear viscosity is reduced in order to improve productivity and quality. Patent Document 1 discloses a method of reducing the shear viscosity by using a plasticizer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 7-292226 Summary of the Invention [Problem to be solved by the invention]
[0005] When the plasticizer of Patent Document 1 is added to a film, unevenness in the film thickness tends to occur. Therefore, an object of the present invention is to provide a polyester film or a polyester film containing recycled materials that has extremely small unevenness in thickness. [Means for solving the problem]
[0006] In order to solve the above problems, the present invention has the following features. (1) A polyester film having an intrinsic viscosity IV of 0.55 dl / g or more and 0.65 dl / g or less, and a shear viscosity ηH (Pa s) at a shear rate of 31.4 rad / s at 280°C of 50 Pa s or more and 220 Pa s or less. (2) The polyester film according to (1), wherein the shear viscosity ηH (Pa s) and the intrinsic viscosity IV (dl / g) of the polyester film satisfy the following formula (A): 5×IV-1.04≦lоg(ηH)≦5×IV-0.92...Formula (A) (3) The polyester film according to (1) or (2), wherein the ratio ηH / ηL of the high-speed shear viscosity ηH to the low-speed shear viscosity ηL is 0.90 or more and 1.00 or less. However, the measurement temperature was 280°C, the high speed was 31.4 rad / s, and the low speed was 0.314 rad / s. (4) The polyester film according to any one of (1) to (3), wherein both of a high-speed shear viscosity ηH and a low-speed shear viscosity ηL are 70 Pa·s or more and 170 Pa·s or less. However, the measurement temperature was 280°C, the high speed was 31.4 rad / s, and the low speed was 0.314 rad / s. (5) The polyester film according to any one of (1) to (4), which has a width of 400 mm or more and an in-plane variation coefficient of thickness measured continuously over a length of 1000 m in the longitudinal direction of the film of 0.8% or less. (6) The polyester film according to any one of (1) to (5), having a thickness of 2 μm or more and 500 μm or less. (7) The polyester film according to any one of (1) to (6), having a particle content of 0.3% by mass or less. (8) The polyester film according to any one of (1) to (7), which is used for optical purposes, for release of multilayer ceramic capacitors, or for producing materials for all-solid-state batteries. Effect of the Invention
[0007] According to the present invention, it is possible to provide a polyester film or a polyester film containing recycled materials having extremely small thickness unevenness. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The polyester film of the present invention will be described in detail below with reference to specific examples.
[0009] In the polyester film of the present invention, the polyester is a polyester composed of a dibasic acid and a glycol, and examples of the aromatic dibasic acid that can be used include terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, diphenyldicarboxylic acid, diphenylsulfonedicarboxylic acid, diphenyletherdicarboxylic acid, diphenylketonedicarboxylic acid, phenylindanedicarboxylic acid, sodium sulfoisophthalic acid, dibromoterephthalic acid, etc. Examples of the alicyclic dibasic acid that can be used include oxalic acid, succinic acid, adipic acid, azelaic acid, suberic acid, sebacic acid, dimer acid, dodecanedioic acid, cyclohexanedicarboxylic acid, etc. As the glycol, as the aliphatic diol, ethylene glycol, propylene glycol, tetramethylene glycol, propylene glycol, tetramethylene glycol, hexamethylene glycol, neopentyl glycol, diethylene glycol, etc. can be used. As the aromatic diol, naphthalene diol, 2,2-bis(4-hydroxydiphenyl)propane, 2,2-bis(4-hydroxyethoxyphenyl)propane, bis(4-hydroxyphenyl)sulfone, hydroquinone, etc. can be used. As the alicyclic diol, cyclohexanedimethanol, cyclohexanediol, spiroglycol, etc. can be used.
[0010] Among these, from the viewpoints of mechanical properties, dimensional stability, and transparency, polyesters selected from polyethylene terephthalate (PET) and copolymers thereof, polyethylene naphthalate and copolymers thereof, polybutylene terephthalate and copolymers thereof, polybutylene naphthalate and copolymers thereof, polyhexamethylene terephthalate and copolymers thereof, and polyhexamethylene naphthalate and copolymers thereof are preferably used.
[0011] The film in the polyester film of the present invention refers to a sheet-like molded product having the above-mentioned polyester resin as the main component (a component contained in an amount of more than 50% by mass and not more than 100% by mass). As secondary components, various additives such as antioxidants, heat stabilizers, weather stabilizers, UV absorbers, organic lubricants, pigments, dyes, inorganic particles, organic particles, fillers, antistatic agents, nucleating agents, etc. may be contained to the extent that they do not deteriorate the properties.
[0012] The particles contained in the polyester film of the present invention are not particularly limited, and either inorganic particles or organic particles can be used, and two or more types of particles can be used in combination. As inorganic particles, for example, clay, mica, wet and dry silica, colloidal silica, aluminum silicate, calcium carbonate, calcium phosphate, barium sulfate, alumina, alumina silicate, zirconia, talc, montmorillonite, titanium oxide, carbon black, and metal stearates such as magnesium stearate and zinc stearate can be used. As organic particles, particles containing resins or compounds such as styrene, polyethylene, silicone, acrylic acid, methacrylic acid, polyester, divinyl compounds, polyimide, polyamide, Teflon (registered trademark), benzoguanine, urethane, and cellulose can be used as constituents.
[0013] The polyester film of the present invention preferably has a particle content of 0.3% by mass or less, and may be substantially free of particles. The term "substantially free of particles" means, for example, in the case of inorganic particles, a content of 50 ppm by mass or less (hereinafter simply referred to as ppm), preferably 10 ppm or less, and most preferably below the detection limit when inorganic elements are quantified by fluorescent X-ray analysis. This is because even if particles are not actively added to the film, contaminants derived from foreign matter, or dirt attached to the raw material resin or the line or equipment in the film manufacturing process may peel off and be mixed into the film. However, from the viewpoint of the slipperiness of the film and the ease of escape of the accompanying air when the film is wound into a roll, the particle content is more preferably 0.01% by mass or more, and the particle content can be appropriately adjusted within a range that does not impair properties such as transparency and surface smoothness. If the particle content exceeds 0.3% by mass, the particles are likely to aggregate, and coarse protrusions may be formed on the film surface, which may be undesirable for use in applications requiring high quality. When the polyester film of the present invention has a laminated structure composed of a plurality of layers, the particle content in the surface layer portion is preferably 0.3% by mass or less for the same reasons as above.
[0014] The volume average particle diameter of the particles added to the polyester film of the present invention is preferably 0.01 μm or more and less than 5.0 μm, and more preferably 0.01 μm or more and 3.0 μm or less. If the volume average particle diameter of the particles is less than 0.01 μm, the film may not exhibit slipperiness, which is not preferable. If the volume average particle diameter is more than 5.0 μm, the accuracy of the filtration filter for the molten resin must be reduced, the efficiency of collecting foreign matter decreases, and the protrusions of the coarse particles on the film surface themselves cause thickness unevenness, which may be unfavorable in use.
[0015] A method for obtaining a polyester resin containing particles includes, for example, dispersing particles in a slurry form in ethylene glycol, which is a diol component, at a predetermined ratio, and adding this ethylene glycol slurry at an arbitrary stage before the completion of polymerization of the polyester resin. In order to improve the dispersibility of particles in a polyester resin containing particles, it is effective to lower the particle concentration in the resin, or to add the water sol or alcohol sol obtained during the synthesis of the particles without first drying them.
[0016] The polyester film of the present invention is preferably a biaxially oriented polyester film. The biaxially oriented polyester film refers to a polyester film that shows a biaxially oriented pattern by wide-angle X-ray diffraction, and is generally obtained by stretching an unstretched polyester sheet in the longitudinal and transverse directions by 2 to 7 times, particularly preferably 3 to 6 times, and then subjecting it to heat treatment to complete the crystal orientation. Here, the longitudinal direction refers to the direction in which the film runs in the manufacturing process (the winding direction in the case of a film roll), and the transverse direction refers to the direction perpendicular to the longitudinal direction within the film plane. The biaxial orientation of the polyester film improves mechanical strength and dimensional stability, and improves flatness.
[0017] The polyester film of the present invention may be a single layer or a laminated structure of two or more layers, but in particular in the case of a structure of two or more layers, the shape of the protrusions on the film surface can be easily controlled by controlling the amount of added particles in the surface layer. In the case of three or more layers, the inner layer can be easily mixed and used with the edge scraps of the film held by the clips in the stretching process, the scraps of film generated from the start of film formation until the product is harvested, the recycled polyester resin of the scraps of film rolls that have failed product inspection, and / or the recycled polyester resin of used film, within a range that does not adversely affect the characteristics of the film surface, which is advantageous in terms of cost and is preferable. In order to prevent the formation of coarse protrusions on the film surface, the particle content of the surface layer can be set to 0.3 mass% or less, and the outermost layer can also contain the recycled polyester resin and / or the recycled polyester resin. In the case of a laminate of two or more layers, each layer may be a polymer of a different type or the same type chemically. In the present invention, a film manufactured using at least one of the scraps of film, the recycled polyester resin, and the recycled polyester resin may be simply called a recycled film.
[0018] The recycled polyester resin generated in the film manufacturing process can be recycled by mixing it with virgin polyester resin at appropriate times, as described in JP 2016-175066 A, in which flakes crushed by a crusher are compressed and cut in a granulator to form pellets (for example, cylindrical molded objects with a height of 30 mm or less), or by melting and kneading flakes crushed by a crusher in an extruder, filtering out coarse particles and foreign matter with a filter, discharging them in the form of strands from a die, and cutting them while cooling to form chips. However, since these recycled polyester resins are subjected to a thermal history and have become low molecular weight, it is inevitable that both the IV and shear viscosity will decrease each time the recycled polyester resin is repeatedly used to manufacture a film with a self-recycling rate of 100%. However, by adding virgin polyester resin and / or recycled polyester resin from used films, which will be described later, and adjusting the content of each resin relative to the total mass of the polyester resin constituting the film, a polyester film with a preferred range of IV and shear viscosity can be manufactured.
[0019] Therefore, it is preferable to increase the content of recycled polyester resin in the polyester resin constituting the film from the viewpoints of reducing costs and the environmental impact, but it is advisable to determine the upper limit of the content within a range that does not impair the required properties for each application of the film, such as thickness unevenness, mechanical properties, dimensional stability, transparency, and surface smoothness.
[0020] In the present invention, the surface layer of the polyester film may further include a lubrication layer, an adhesive layer, a release layer, a functional layer, etc. The lubrication layer may include a water-soluble resin to which a certain amount of inorganic particles or organic particles are added, the adhesive layer may include a water-soluble resin to which a functional group is added, the release layer may include a silicone release functional resin or a silicone-free release functional resin, and the functional layer may include a hard-coated curable resin, a thermoplastic resin utilizing refraction, or a curable resin.
[0021] The method for forming a slippery layer, an adhesive layer, a release layer, a functional layer, etc. on the surface layer of the polyester film is not particularly limited as long as it does not impair the effects of the present invention, and for example, a co-extrusion method, a coating method, a dry lamination method, a melt lamination method, etc. can be used. Among them, it is preferable to use a coating method because the procedure is simple. As a method for applying the coating agent, a method such as a roll coater, a gravure coater, or a bar coater can be used. The application process can be appropriately selected, such as before stretching the polyester film, during the stretching process, or after stretching and heat treatment.
[0022] The intrinsic viscosity IV of the polyester film of the present invention is preferably 0.55 dl / g or more and 0.65 dl / g or less. When the IV of the film is less than 0.55 dl / g, the molecular chain of the polyester resin used is short, which is likely to cause thickness unevenness during film production or recycled film production. In addition, the molecular mobility is likely to increase, which deteriorates heat resistance, and the flatness and mechanical properties during heating tend to be easily reduced. On the other hand, when the IV of the film exceeds 0.65 dl / g, the molecular chain of the polyester resin used is long and the molecular mobility is low, which improves heat resistance and improves flatness and mechanical properties during heating, but the biaxial orientation is low, which may easily cause thickness unevenness during film production or recycled film production. In addition, when the IV of the film exceeds 0.65 dl / g, if the film is thinned, breaks starting from thickness unevenness during film production may increase, which may easily deteriorate productivity. The intrinsic viscosity IV is measured by the method described in the examples.
[0023] The polyester film of the present invention preferably has a shear viscosity ηH (Pa·s) of 50 Pa·s or more and 220 Pa·s or less at a shear rate of 31.4 rad / s at 280°C. If ηH is less than 50 Pa·s, the flowability of the polyester resin is high, and when the polyester resin is discharged as a sheet-shaped molten resin onto a rotating cooling body such as a casting drum, the thickness may become uneven due to the film vibration of the polymer. On the other hand, if ηH exceeds 220 Pa·s, the filtration pressure of the filter used in the filtration process of the polymer increases, and some of the foreign matter trapped in the filter may leave the filter due to the pressure and flow out to the downstream side (secondary side), and the foreign matter may be included in the product, thereby reducing the quality and value of the product. The shear viscosity is measured by the method described in the examples.
[0024] In the polyester film of the present invention, it is preferable that the shear viscosity ηH (Pa·s) at a shear rate of 31.4 rad / s at 280° C. and the intrinsic viscosity IV (dl / g) of the polyester film satisfy the following formula (A). 5×IV-1.04≦lоg(ηH)≦5×IV-0.92...Formula (A) When log(ηH) is less than 5×IV-1.04, the polyester resin has high fluidity, and when it is discharged as a sheet-shaped molten resin onto a rotating cooling body such as a casting drum, the polymer film vibration may cause large thickness unevenness. On the other hand, when log(ηH) exceeds 5×IV-0.92, the filtration pressure of the filter used in the polymer filtration process increases, and some of the foreign matter trapped in the filter may leave the filter due to the pressure and flow out to the downstream side (secondary side), and this foreign matter may be included in the product, reducing the grade and value of the product.
[0025] The shear viscosity of the polyester film of the present invention is preferably such that the ratio ηH / ηL of the shear viscosity at high speed ηH to the shear viscosity at low speed ηL is 0.90 or more and 1.00 or less. However, the measurement temperature is 280° C., the speed at high speed is 31.4 rad / s, and the speed at low speed is 0.314 rad / s. By having ηH / ηL of 0.90 or more and 1.00 or less, the extruder screw rotation speed can be adapted from low to high speeds, that is, it can be adapted to a wide range of film thickness, width, and film formation speed, and the molten resin can be extruded after devolatilization, melting, kneading, mixing, and dispersion with less uneven discharge and property changes of the molten resin.
[0026] In addition to the above reasons, from the viewpoint of reducing changes over time in thickness unevenness and the number of foreign objects, etc., and stabilizing the production of recycled films over the long term, it is preferable that the shear viscosity at high speed ηH and the shear viscosity at low speed ηL are both 70 Pa·s or more and 170 Pa·s or less. However, the measurement temperature is 280°C, the high speed is 31.4 rad / s, and the low speed is 0.314 rad / s. By having both of them be 70 Pa·s or more, thickness unevenness caused by film vibration of the polymer can be further suppressed, and by having both be 170 Pa·s or less, the extrusion of foreign objects trapped in the filter can be suppressed.
[0027] The virgin polyester resin constituting the polyester film of the present invention can be produced by a known method. For example, in the case of PET, the esterification step is carried out under stirring using one or more esterification reaction tanks. For example, when a single esterification reaction tank is used, the reaction temperature is usually 240° C. or higher and 280° C. or lower, the relative pressure to atmospheric pressure is usually 0 kPa or higher and 400 kPa or lower, and the reaction time is usually 1 hour or higher and 10 hours or lower. The esterification reaction rate of the esterification reaction product obtained in the esterification step is usually 95% or higher.
[0028] The melt polycondensation step can usually be carried out in a continuous or batch manner using one or more polycondensation reaction tanks, and is carried out while gradually reducing the pressure from normal pressure and distilling the ethylene glycol produced under heating and stirring out of the system. For example, in the case of a batch manner using a single polycondensation reaction tank, the reaction temperature is usually 250°C to 290°C, the final absolute pressure gradually reduced from normal pressure is usually 1.3 kPa to 0.013 kPa (10 Torr to 0.1 Torr), and the reaction time is usually 1 hour to 20 hours.
[0029] The IV and shear viscosity of the virgin polyester resin can be determined by the stirring torque of the polymer at the end of polymerization. When the stirring torque is high, the IV of the polymer is high and the shear viscosity is also high. The stirring torque for determining the end point of the polymerization device may be set so that the IV and shear viscosity are the target IV and shear viscosity. In order to obtain the polyester film of the present invention, it is preferable to set the stirring torque for determining the end point so that the IV and shear viscosity of the virgin polyester resin as the raw material are slightly higher than the IV and shear viscosity of the film. In general, the increase and decrease trends of the IV and shear viscosity are similar, but depending on the type and amount of additives, the IV may change even if the target shear viscosity is achieved.
[0030] The resulting virgin polyester resin after polymerization is discharged in the form of strands from the bottom of the polymerization apparatus and cut with a cutter while being cooled with water. Since the chip shape can be controlled by cutting, a virgin polyester resin having a preferred bulk density in the present invention can be obtained.
[0031] The polycondensation catalyst used in the present invention may be one or more of antimony trioxide, antimony pentoxide, antimony acetate, antimony glycolate, germanium dioxide, and organic titanium compounds. When an antimony compound and / or a germanium compound is used, the sum of the contents of antimony element and germanium element relative to the total mass of the polyester resin constituting the film is preferably 20 ppm or more and 200 ppm or less in terms of polycondensation reactivity and solid-phase polymerization reactivity, and more preferably 50 ppm or more and 150 ppm in terms of heat resistance and hydrolysis resistance. If it exceeds 200 ppm, the polycondensation reactivity and solid-phase polymerization reactivity are improved, but the decomposition reaction during remelting is also promoted, so that the number of carboxyl end groups increases, which causes a decrease in heat resistance and hydrolysis resistance, and may also form foreign matter due to aggregation.
[0032] The polyester film of the present invention may contain, as additives, one or more of metal compounds such as manganese, magnesium, calcium, and cobalt, or alkali metal salts, alkaline earth metal salts, and silicone compounds, such as lithium acetate, sodium acetate, potassium acetate, potassium hydroxide, magnesium acetate, magnesium hydroxide, magnesium alkoxide, magnesium carbonate, potassium hydroxide, calcium hydroxide, calcium acetate, calcium carbonate, manganese oxide, manganese acetate, polydimethylsiloxane, polydiethylsiloxane, polymethylphenylsiloxane, polyorganosiloxane, and reactive silicones having functional groups at both ends or one end that react with the organic groups of the polyester resin. When a magnesium compound and / or a manganese compound is used, the sum of the contents of magnesium element and manganese element relative to the total mass of the polyester resin constituting the film is preferably 10 ppm or more and 150 ppm or less, more preferably 30 ppm or more and 130 ppm or less. From the viewpoint of improving the electrostatic applicability for adhering the sheet-shaped molten resin to the casting drum and suppressing thermal decomposition, it is preferable that the content is 10 ppm or more, and from the viewpoint of suppressing foreign matter due to aggregation of metal compounds, it is preferable that the content is 150 ppm or less. When a silicone-based compound is used, the content of silicon element relative to the total mass of the polyester resin constituting the film is preferably 5 ppm or more and 100 ppm or less. The silicon element is an element derived from a silicone compound. From the viewpoint of promoting the reduction of shear viscosity, it is preferable that the content is 5 ppm or more, and from the viewpoint of suppressing bleed-out of the silicone compound when the film is used, it is preferable that the content is 100 ppm or less. By containing silicone, which is generally often used as a mold release agent, in the polyester resin, the wall surface slipperiness in the molten state, that is, the fluidity, is improved and the shear viscosity can be reduced. From the viewpoint of maintaining the intrinsic viscosity, it is preferable to use a silicone compound whose weight average molecular weight is close to that of polyester, and for example, when the polyester is PET, it is preferable to use a silicone compound whose weight average molecular weight is 30,000 to 50,000.The weight average molecular weight of the silicone compound can be adjusted by the method described in, for example, JP-A-2007-146049.
[0033] In the polyester film of the present invention, phosphorus compounds may be used as stabilizers, such as phosphoric acid, trimethyl phosphate, triethyl phosphate, tri-n-butyl phosphate, trioctyl phosphate, triphenyl phosphate, tricresyl phosphate, dibutyl phosphate, monobutyl phosphate, triethyl phosphonoacetate, tris(triethylene glycol) phosphate, phosphorous acid, dioctyl phosphate, triphenyl phosphite, tris-dodecyl phosphite, tris-nonylphenyl phosphite, methyl acid phosphate, ethyl acid phosphate, triethylene glycol acid phosphate, isopropyl acid phosphate, and butyl acid phosphate. The content of phosphorus element relative to the total mass of the polyester resin constituting the film is preferably 5 ppm or more and 100 ppm or less, and more preferably 5 ppm or more and 50 ppm or less. By setting the content as described above, it is possible to prevent the phosphorus compound from becoming foreign matter and the polymerization activity from decreasing. In addition, ppm is based on mass.
[0034] In the present invention, in order to suppress the amount of terephthalic acid generated by the decomposition reaction of the polymer when the film after melt casting is heated, an alkali metal phosphate is added in addition to the phosphorus compound generally added during polyester polymerization, which improves hydrolysis resistance and thermal decomposition resistance, suppresses the amount of terephthalic acid generated when the film is heat-treated or heat-processed, and can maintain a more suitable terephthalic acid concentration, so it is preferable to contain an alkali metal phosphate. The content of the alkali metal element relative to the total mass of the polyester resin constituting the film is preferably 5 ppm or more and 50 ppm or less, more preferably 10 ppm or more and 40 ppm or less, from the viewpoint of the amount of oligomer generated during heating or heat processing of the film.
[0035] The alkali metal phosphate in the present invention is not particularly limited, but examples thereof include sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, lithium dihydrogen phosphate, dilithium hydrogen phosphate, and trilithium phosphate. Among these, sodium dihydrogen phosphate and potassium dihydrogen phosphate are preferred from the viewpoint of hydrolysis resistance.
[0036] The polyester film of the present invention may contain recycled polyester resin from used films or PET bottles. From the viewpoint of reducing the environmental load, it is preferable to determine the upper limit of the content within a range that does not impair the required properties for each film application, such as thickness unevenness, mechanical properties, dimensional stability, transparency, and surface smoothness. The recycled polyester resin may contain the same polycondensation reaction catalyst, additives, stabilizers, and alkali metal phosphate as the virgin polyester resin.
[0037] A used film refers to a film that has been used as a product for a specific purpose. By recycling a film that has been used as a product for a specific purpose and that would otherwise be discarded, it is possible to reduce the environmental load. Examples of used films include a hard coat layer, a refraction adjustment layer, and an easy-adhesion layer that facilitates lamination with other members, which are typical functional layers of optical films, and in release films, the substrate of a used adhesive tape, the release paper of an adhesive tape, and a film for a product manufacturing process. Among these, films for product manufacturing processes, particularly release films for multilayer ceramic capacitor manufacturing processes and polarizing film manufacturing processes, have been used in increasing amounts in recent years, and are therefore preferable because recycling can reduce the amount of waste, which leads to a reduction in the environmental load. When the used film is a release film used in the manufacturing process of a multilayer ceramic capacitor, the composition contained as an impurity includes barium titanate, which is a component of the object to be released, and silicone, which is a component of the release agent. When a film is obtained from a recycled polyester resin of a used film containing a large amount of such release agent components and released material components, a large amount of foreign matter is generated, so it is preferable to remove the sum of the contents of impurity elements such as barium element and titanium element, excluding silicon element derived from silicone, in the entire recycled polyester resin to 10 ppm or less, more preferably 5 ppm or less. When promoting the reduction of the shear viscosity of the recycled polyester resin, the content of silicon element derived from silicone is preferably 5 ppm or more to express the effect, and is preferably 100 ppm or less from the viewpoint of suppressing the bleed-out of silicone compounds when the film is used.
[0038] Chemical recycling and mechanical recycling are known as methods for recycling used films and PET bottles. In the chemical recycling method, used films are chemically decomposed, returned to raw materials (monomers), and polyester is repolymerized. It is possible to obtain recycled polyester resin that is the same as virgin polyester resin, but there is a problem that the process is longer and the cost is higher than that of producing virgin polyester resin. The mechanical recycling method is, for example, a method described in JP 2023-81479 A, in which a coating (impurities) is removed from the surface of used film crushed into flakes using an alkaline aqueous solution, and trace amounts of residual coating and alkaline components are removed by washing with water. Next, the water is dried to volatilize the water, melted and kneaded in an extruder, and coarse particles and foreign matter are filtered out with a filter, and then the mixture is discharged from a die in the form of strands, cut while cooling, and chipped, and recycled polyester resin can be obtained at a lower cost than the chemical recycling method. As another method, for example, the method described in JP 2023-142608 A can be used to unwind a film from a used film roll, remove the coating while transporting it in a water tank containing a cleaning solution by roll to roll, dry and pulverize it, and perform the chipping process in a similar manner to obtain a recycled polyester resin. In addition, when a silicone compound is contained in the coating of the used film, the content of silicon element derived from silicone in the entire recycled polyester resin can be adjusted by the alkali concentration, temperature, and treatment time of the alkaline aqueous solution used. Therefore, when a recycled polyester resin is used for the polyester film of the present invention, a mechanically recycled recycled polyester resin is more preferably used, although not particularly limited.
[0039] As the type of alkaline aqueous solution used in mechanical recycling, from the viewpoint of improving the peelability of the coating, an aqueous solution of lithium hydroxide, sodium hydroxide, potassium hydroxide, etc. may be mentioned, and sodium hydroxide is preferable.
[0040] The concentration of the alkaline aqueous solution used is preferably 0.5% by mass or more and 6.0% by mass or less. If it is less than 0.5% by mass, the peelability of the coating film may decrease and peeling may take a long time. If it exceeds 6.0% by mass, hydrolysis may be promoted, which may cause a decrease in the molecular weight and IV of the polyester support.
[0041] The alkaline aqueous solution preferably contains a surfactant. The content is preferably 0.01% by mass or more and 0.10% by mass or less based on the total amount of the alkaline aqueous solution. The addition of a surfactant increases the permeability of the alkaline aqueous solution to the interface between the polyester support and the coating, thereby promoting peeling and suppressing re-adhesion of the peeled coating to the polyester support. The types of surfactant include nonionic surfactants, anionic surfactants, cationic surfactants, etc., and preferably nonionic and anionic surfactants. Examples of nonionic surfactants include polyethylene glycol ethers, particularly polyethylene glycol ethers of higher alcohols, and polyethylene glycol ethers of alkylphenols. Examples of anionic surfactants include alkylbenzene sulfonates and alkyl sulfates. In order to prevent precipitation of the surfactant in the alkaline aqueous solution and re-adhesion of impurities insoluble in alkali, it is recommended to perform stirring and washing in a washing tank equipped with stirring blades.
[0042] The temperature of the alkaline aqueous solution is preferably 60° C. or more and 98° C. or less. If it is less than 60° C., the peelability of the coating laminated on the polyester support may decrease, and peeling may take a long time. If it is more than 98° C., the temperature approaches the boiling point, so a pressurized cleaning tank is required and heating may cause hydrolysis or dissolution of the polyester support.
[0043] The time for the treatment by stirring and washing is preferably 15 minutes or more and 30 minutes or less when the washing concentration is 10 mass % or less (1 mass part of the washing material is 9 mass parts or more of the alkaline aqueous solution containing a surfactant). By setting it in the above range, the coating can be efficiently removed from the polyester support.
[0044] After washing with the alkaline aqueous solution, it is preferable to wash with water. In the water washing, traces of the coating remaining on the polyester support are removed, and the adhering alkaline components are removed. As with the alkaline washing, a washing tank equipped with an agitator blade can be used. From the viewpoint of cleaning time and cost, it is preferable to carry out the washing in one stage. Furthermore, it is preferable that the agitator rotation speed is in the range of 100 rpm to 300 rpm for both the alkaline washing and the water washing, and the treatment time by the agitator washing is 15 minutes to 30 minutes. By setting the temperature in the above range, the coating can be efficiently removed from the polyester support. After the water washing, it is preferable to vacuum dry at 60°C to 200°C. More preferably, it is 90°C to 120°C.
[0045] The polyester support that has been dried to volatilize the water is melted and kneaded in an extruder, coarse particles and foreign matter are filtered out with a filter, and the polyester support is extruded from a die in the form of a strand, which is then cut while being cooled, to obtain a recycled polyester resin. When a silicone compound is contained in the coating of a used film, a recycled polyester resin that intentionally contains silicon element derived from silicone at 5 ppm to 100 ppm can be obtained within the above-mentioned ranges of concentration, temperature, and treatment time of the alkaline aqueous solution.
[0046] A preferred embodiment of the polyester film of the present invention is one in which the film width is 400 mm or more, and the coefficient of variation in the surface thickness measured continuously over a length of 1000 m in the longitudinal direction of the film is 0.8% or less. Here, the coefficient of variation in the surface thickness measured continuously over a length of 1000 m in the longitudinal direction of the film refers to the thickness measured continuously and non-contact with respect to the entire width of the film. Conventionally, the thickness of a polyester film was measured by scanning a non-contact thickness gauge in the width direction during film formation, or by cutting a sample in the longitudinal direction from a film roll and measuring it with a contact thickness gauge. However, with the development of thickness measurement technology, it has become possible to continuously measure the entire width in the longitudinal direction, and it has become possible to understand the thickness unevenness behavior over the entire film surface, which could not be confirmed before. The coefficient of variation in the film surface is preferably 0.8% or less, more preferably 0.5% or less. If the coefficient of variation exceeds 0.8%, it may affect color unevenness in optical films, and may affect lamination thickness unevenness when a release object is placed on the film for release. In particular, in the case of release films for laminated ceramic capacitors, the surface dimensions of capacitor elements are becoming smaller, down to 0.2 mm x 0.1 mm, and the number of laminated ceramic layers and electrode layers is also increasing to increase capacity, so the lower the coefficient of variation in the surface thickness of the film, the more the unevenness in the laminated thickness of the ceramic layers and electrode layers and the variation in the electrical properties of each capacitor element can be reduced. Note that the coefficient of variation in the surface thickness is determined by the method described in the Examples.
[0047] The film width of the intermediate roll is 400 mm or more and 10,000 mm or less, and the length in the longitudinal direction of the film is 1,000 m or more and 100,000 m or less. After obtaining the intermediate roll, it can be slit into the desired width and length to obtain the product roll. Generally, from the viewpoint of roll transportability, etc., the width is 400 mm or more and 3,000 mm or less, and the length is 1,000 m or more and 50,000 m or less.
[0048] The thickness of the polyester film of the present invention is not particularly limited, but is preferably 2 μm or more and 500 μm or less. When the polyester film of the present invention is used for optical purposes or release purposes, it is more preferably 10 μm or more and 200 μm or less. If the thickness of the film is less than 2 μm, the transportability may be poor, resulting in wrinkles, or holes due to insufficient heat resistance may occur. On the other hand, if the thickness of the film exceeds 500 μm, the transparency and processability may be impaired. By setting the film thickness within the above range, the occurrence of wrinkles and holes can be suppressed, and the transparency and processability can be improved. In addition, as a method for adjusting the thickness of the film to 2 μm or more and 500 μm or less, it can be adjusted by controlling the amount of polymer discharged from the T-die so as to obtain a target thickness while measuring the thickness of the film after biaxial stretching with a non-contact thickness meter.
[0049] Next, a method for producing the polyester film of the present invention will be described, but the present invention is not limited to such an example.
[0050] Virgin polyester resin, recycled polyester resin, and recycled polyester resin are mixed in a predetermined ratio, dried, and then fed to a known extruder. The extruder used in the production of the polyester film of the present invention may be a single-screw or twin-screw extruder. In addition, in order to omit the drying process of the polyester resin, a vent-type extruder equipped with a vacuum line may be used. When producing a film having two or more layers, a tandem extruder may be used for the layer with the largest extrusion amount, in which the function of melting the polyester resin and the function of keeping the molten resin at a constant temperature are shared by each extruder. The tandem extruder is preferable as a process for reducing thickness unevenness because it stabilizes the temperature of the molten resin during high discharge and, as a result, it is possible to reduce the viscosity variation of the molten resin. When the melting point of the polyester resin is Tm, the melting temperature is preferably Tm or more and Tm+45°C or less. If it is less than Tm, the resin does not melt, and if it exceeds Tm+45°C, the resin decomposes and deteriorates, causing IV and a significant decrease in shear viscosity. Furthermore, the resin may not be uniformly heated before reaching the T-die, which may affect thickness unevenness.
[0051] The molten resin discharged from the extruder is filtered through a filter. Even the smallest foreign matter will become large protrusions when it enters the film, so it is effective to use a filter with a high-precision collection efficiency that captures 95% or more of foreign matter of 5 μm or more. On the other hand, if the collection efficiency of the filter is too high, the degree of pressure rise may increase, so the use of a filter with a higher precision collection efficiency that captures 95% or more of foreign matter less than 5 μm may be an embodiment that is not preferable in terms of suppressing thickness unevenness. Next, the film is extruded into a sheet from a T-die and cooled and solidified on a casting drum to obtain an unstretched film. For example, in the case of a three-layer laminate, three extruders and a three-layer manifold or junction block (for example, a junction block having a rectangular junction portion) are used to laminate the three layers, and a sheet is extruded from a T-die. Alternatively, two extruders, one of which is a three-layer manifold or junction block in which polyester resin supplied from one extruder is laminated on both surface layers, can be used to laminate the three layers, and a sheet can be extruded from a T-die. In this case, it is preferable that the lip gap of the T-die can be automatically adjusted by a heater. Furthermore, it is desirable to be able to feed back the film thickness after stretching to the lip gap of the T-die in order to suppress thickness unevenness. In addition, it is desirable to surface treat the lip of the T-die with tungsten carbide and reduce the corner R of the lip tip in terms of suppressing streaks that adhere to and grow on the lip. The sheet extruded from the T-die is cooled in a casting drum to produce an unstretched film. In this case, from the viewpoint of stabilizing the back pressure and suppressing thickness fluctuation, a method of installing a static mixer and a gear pump in the flow path of the molten resin is effective as a means for suppressing thickness unevenness in the longitudinal direction in the present invention. The gear pump has a function of blocking pressure fluctuations in the extrusion process, so it is important for uniformly controlling the longitudinal thickness, and the longitudinal thickness unevenness can be suppressed to a small value by keeping the rotation speed of the gear built into the gear pump constant.
[0052] Regarding the rotation accuracy of the casting drum, the speed fluctuation and surface irregularities of the casting drum due to the eccentricity of the casting drum may affect the thickness unevenness in the longitudinal direction. Since the speed fluctuation of the casting drum surface has a large effect on the thickness unevenness in the longitudinal direction, it is a preferred embodiment to attach a balance weight to any circumferential location on the end face of the casting drum to reduce the unevenness due to the eccentricity. In addition, it is also a preferred embodiment to use two motors for rotating the casting drum and separate the functions of driving and braking in order to suppress the thickness unevenness in the longitudinal direction.
[0053] The unstretched film that has landed on the casting drum is adhered to the drum by electrostatic force using a pinning device. The pinning device applies a charge from an electrostatically applied wire or tape onto the casting drum over the entire width of the unstretched film, and the film is adhered to the casting drum by static electricity at the interface between the casting drum and the film. In this case, in order to keep the intensity of the charge constant in the width direction, it is preferable that the distance from the electrostatically applied wire or tape to the film is equal over the entire width of the unstretched film. In addition, in order to maintain the adhesion between the casting drum and the film at an appropriate strength, it is preferable to adjust the strength of the electrostatically applied current, and since the electrostatically applied wire or tape is contaminated by oligomers generated from the unstretched film, it is preferable to use it while winding it in one direction. The film that has been adhered to the casting drum and cooled is peeled off from the casting drum using a peeling roll, and is introduced to the next stretching process. In this case, water may be passed through the peeling roll to cool the film, or the peeling roll may be driven.
[0054] Thereafter, the unstretched film is stretched biaxially in the longitudinal direction and the width direction, and then heat-treated. The stretching process may be simultaneous biaxial stretching or sequential biaxial stretching. In simultaneous biaxial stretching, since stretching by rolls is not involved, local heating of the film surface or stretching unevenness due to uneven rotation of the rolls does not occur, and thickness unevenness is easily controlled, making it a more preferable stretching method.
[0055] In the simultaneous biaxial stretching, both ends of the unstretched film in the width direction are held by clips on each side of the tenter device, and the unstretched film is preheated by applying hot air, and then the film is stretched simultaneously in the longitudinal direction and the width direction at a stretching temperature of Tg or more and Tg+140°C or less, more preferably Tg or more and Tg+70°C or less, where Tg is the glass transition temperature of the polyester resin. Setting the stretching temperature at Tg or more is preferable in terms of suppressing breakage of the film, and setting the stretching temperature at Tg+140°C or less is preferable in terms of obtaining sufficient strength. In addition, from the viewpoint of reducing stretching unevenness, the total stretching ratio (area stretching ratio) in the longitudinal direction and the width direction is preferably, for example, 8 times or more and 30 times or less. By setting the area stretching ratio at 8 times or more, good thickness unevenness and sufficient strength can be obtained, and by setting it at 30 times or less, breakage of the film during the manufacturing process can be reduced.
[0056] Then, when the melting point of the polyester resin is Tm, the film is heat-set at Tm-80°C or higher and Tm-20°C or lower for, for example, 0.5 seconds or more and 20 seconds or less. By setting the heat-setting temperature at Tm-80°C or higher, the crystallization of the film can be promoted to stabilize the structure. In addition, by setting the heat-setting temperature at Tm-20°C or lower, the decrease in Young's modulus caused by the relaxation of the amorphous chain part of the polyester can be suppressed, so that sufficient strength can be obtained. Then, in order to adjust the dimensional change rate and flatness, a relaxation treatment may be performed in the longitudinal direction and / or width direction at, for example, 50°C or higher and lower than the heat-setting temperature, for example, 0% or more and 10% or less, in the intermediate cooling zone or slow cooling zone during or after the heat treatment. In this case, it is preferable to control the temperature difference in the width direction inside the oven to within 5°C in order to improve the thickness unevenness in the width direction.
[0057] Next, the case of sequential biaxial stretching will be described. First, the longitudinal stretching is usually performed by the difference in the peripheral speed of the rolls, and this stretching may be performed in one stage, or may be performed in multiple stages using a plurality of pairs of rolls. When performing the stretching in multiple stages, it is preferable to set the stretching ratio in one stretching section to 3 times or less, since an appropriate stretching tension can be ensured. In order to reduce thickness unevenness in the longitudinal direction, a driving method in which the roll peripheral speed can be set individually for each roll is preferable. In the longitudinal stretching process, the material of the transport roll is selected by either heating the unstretched film to Tg or higher before stretching, or transporting the film to the stretching zone while maintaining the temperature below Tg, and heating it all at once using a heater during stretching. The stretching ratio is, for example, 2 times or more and 7 times or less, particularly preferably 3 times or more and 6 times or less, and the stretching temperature is, for example, Tg or more and Tg+60°C or less.
[0058] Next, the film is conveyed while being held at both ends in the width direction by clips of a tenter device, and the film is preheated to Tg or higher by applying heat, and then stretched in the width direction. The stretching ratio is, for example, 2 times or more and 7 times or less, particularly preferably 3 times or more and 6 times or less, and the stretching temperature is, for example, Tg or more and Tg + 140 ° C or less, particularly preferably Tg or more and T + 70 ° C or less. Furthermore, in order to alleviate bowing that occurs in the transverse stretching process, re-longitudinal stretching and / or re-transverse stretching may be performed, which can reduce the occurrence of thickness unevenness due to local deformation. The process from heat setting to slow cooling thereafter is the same as that for simultaneous biaxial stretching.
[0059] The biaxially stretched film is cooled in a conveying process, and then the edges are cut and wound to obtain an intermediate roll. In this conveying process, the film thickness in the width direction is measured, and the data is fed back to adjust the film thickness by adjusting the T-die thickness, etc., and foreign matter can be detected by a defect detector. The thickness can be measured using β-rays, X-rays, or optical interference. The measurement can be performed by a method in which one measuring device is moved laterally in the width direction to measure the thickness of the entire width, a method in which multiple measuring devices are moved laterally in a section divided in the width direction to measure the thickness of the entire width, or a method in which multiple measuring devices are fixed in the width direction to measure the thickness of the entire width in an inspection device with a wide measurement range. In addition, as for the location where the measurement is performed in the film manufacturing process, it is a preferable embodiment to perform the measurement within the above-mentioned conveying process. The thickness can also be measured by unwinding the film from the intermediate roll and performing the thickness measurement in the conveying process of the slitter or rewinder.
[0060] A preferred embodiment of the method for producing a polyester film according to the present invention comprises a step of melt-extruding 0 to 75 parts by mass of a virgin polyester resin having an intrinsic viscosity IV (dl / g) of 0.57 to 0.67 and an ηH (Pa·s) of 120 to 330 and 25 to 100 parts by mass of a recovered or recycled polyester resin having an intrinsic viscosity IV (dl / g) of 0.55 to 0.65 and an ηH (Pa·s) of 100 to 280, relative to 100 parts by mass of the entire polyester film.
[0061] The virgin polyester resin preferably has an ηL (Pa s) of 130 to 330, and an ηH / ηL of 0.90 to 1.00. The recovered or regenerated polyester resin preferably has an ηL (Pa s) of 110 to 280, and an ηH / ηL of 0.90 to 1.00. EXAMPLES
[0062] The present invention will be specifically described below with reference to examples. The measurement methods in the examples are as follows. That is correct.
[0063] (1) Intrinsic viscosity IV (unit: dl / g) The polyester resin or polyester film was dissolved in 100 mL of orthochlorophenol (solution concentration C = 1.2 g / mL), and the viscosity of the solution at 25°C was measured using an Ostwald viscometer. The viscosity of the solvent was also measured in the same manner. Using the obtained solution viscosity and solvent viscosity, [η] was calculated according to the following formula (B), and the obtained value was taken as the intrinsic viscosity IV. ηsp / C=[η]+K[η] 2 ·C ···Formula (B) (Here, ηsp = (solution viscosity / solvent viscosity)-1, and K is the Huggins constant (assumed to be 0.343).) If there is any insoluble matter in the solution in which the polyester resin or polyester film is dissolved, the solution is filtered and the mass of the filtrate is measured, and the value obtained by subtracting the mass of the filtrate from the mass of the sample to be measured is determined as the mass of the sample to be measured.
[0064] (2) Shear viscosity (unit: Pa s) A polyester resin sample or a polyester film sample cut into 40 mm squares and stacked was prepared, and dried in a vacuum dryer at 150°C for 8 hours until immediately before measurement, and then returned to normal pressure with nitrogen, and 0.4 g was immediately weighed. Next, 0.4 g of the sample was filled into the parallel plates (60 mm diameter) of a rheometer: RHEOSOL-G3000 manufactured by UBM Co., Ltd., and the distance between the upper and lower plates was set to 5 mm, and the sample was melted at 280°C for 1 minute in a nitrogen atmosphere. Then, after adjusting the distance between the plates to 0.5 mm, the shear viscosity ηH at a shear rate of 31.4 rad / s and ηL at 0.314 rad / s were measured. Note that ηH and ηL were the arithmetic average of the measurement results obtained by two trials.
[0065] (3) Coefficient of variation of surface thickness (unit: %) The surface thickness was measured using a thickness measurement sensor installed between the transport rolls of the rewinder: a film thickness distribution measuring device FiDiCa manufactured by JFE Techno Research Corporation. The film was unwound from a 1.5m wide intermediate roll by the rewinder at a speed of 50m / min, and measurements were taken over 1000m in the longitudinal direction. The arithmetic mean value of this surface thickness data was taken as the film thickness, and the value obtained by dividing the standard deviation value of the surface thickness data by the arithmetic mean value and converting the result into a percentage was taken as the coefficient of variation of the intermediate roll. The coefficient of variation was calculated from the arithmetic mean value (unit: μm) and standard deviation value (unit: μm) rounded off to the third decimal place.
[0066] The coefficient of variation of the product roll was also determined in the same manner as for the intermediate roll.
[0067] (4) Number of foreign objects (unit: pieces / 1000cm 2 ) The film was measured at 1000cm using a distortion tester TYPE:25WS manufactured by Shinto Chemical Co., Ltd. 2 The foreign matter observed in the polarized visual field was marked and samples were taken. The obtained foreign matter samples were observed under an optical microscope (magnification adjusted appropriately from 20 to 400 times), the dimension in the direction in which the size of the foreign matter was the largest was taken as the long diameter of the foreign matter, and the number of foreign matters with a long diameter of 30 μm or more was counted. Evaluation was performed according to the following criteria. A or higher is acceptable. In addition, elemental analysis of the foreign matter parts of some of the foreign matter samples was performed using a scanning electron microscope (SEM) S-4300A (manufactured by Hitachi, Ltd.) equipped with an energy dispersive X-ray analyzer (EDX) EMAX-7000 (manufactured by Horiba, Ltd.) to measure the presence or absence of silicon element.
[0068] (5) Particle content (unit: mass%) Polyester resin or polyester film is thoroughly washed with methanol to remove surface deposits, and 300 g of the sample is washed and dried with water. 2.7 kg of o-chlorophenol is added and heated to 100°C while stirring. After heating, the sample is left for another hour to dissolve the polyester portion. However, if the polyester portion does not dissolve due to high crystallization, the sample is dissolved once and then rapidly cooled before the dissolution operation. Next, coarse insoluble matter such as dust contained in the polyester is removed by filtration using a G-1 glass filter, and the mass of the filtered matter is subtracted from the mass of the sample. A Hitachi Ltd. 40p separation ultracentrifuge equipped with a rotor RP30 is used, and 30 cc of the solution after the glass filter filtration is poured into each cell, and the rotor is rotated at 4500 rpm. After confirming that there is no abnormality in the rotation, the rotor is evacuated and the rotation speed is increased to 30,000 rpm, and the particles are centrifuged at this rotation speed. The separation is completed after about 40 minutes, but if necessary, this can be confirmed by checking that the light transmittance at 375 nm of the liquid after separation is a constant value higher than that before separation. After separation, the supernatant is removed by decantation to obtain separated particles. Since the separated particles may contain polyester due to insufficient separation, o-chlorophenol at room temperature is added to the collected particles, and after suspending them almost uniformly, they are subjected to ultracentrifugation again. The dried particles are subjected to differential scanning calorimetry, and this must be repeated until the melting peak corresponding to the polymer can no longer be detected. Finally, the separated particles A obtained in this way are vacuum dried at 120°C for 16 hours and weighed, which is the particle content (mass%) in the resin or film.
[0069] (6) Silicon content (unit: ppm) 2.5 g of a polyester resin or polyester film sample was heated in the presence of sulfuric acid at about 150°C for about 1 hour, then hydrogen peroxide solution was gradually added and held for about 30 minutes to incinerate and completely decompose, and the volume was adjusted to 50 ml with distilled water, and the amount was quantified using an ICP emission spectrometer VISTA-PRO manufactured by Varian Technologies Japan Limited, and converted to mass ppm in the polyester sample. Note that if the sample contained particles, the sample was dissolved in a solvent in advance, undissolved particles were centrifuged, and the solvent of the supernatant was evaporated and dried, and the amount was quantified.
[0070] (7) Coefficient of variation of surface thickness of recycled polyester film, number of foreign objects The polyester films produced in each Example and Comparative Example were compressed and cut in a granulator to form cylindrical pellets with a diameter of 5 mm x 20 mm, which were then used as raw materials. Polyester films were produced under the same production conditions as those in each Example and Comparative Example, except that the raw material was used at 100% by mass for the thickest layer, and the (3) coefficient of variation of the surface thickness and (4) number of foreign objects were evaluated for the obtained films in the same manner.
[0071] [Production of polyester resin] The polyester resin used in the production of the polyester films in the examples was produced by the following method. The properties of the resulting polyester resin are shown in Table 1.
[0072] (Virgin polyester resin A) Esterification reaction was carried out with 86 parts by mass of terephthalic acid and 37 parts by mass of ethylene glycol at 255° C. while distilling off water. After completion of the esterification reaction, 0.01 parts by mass of phosphoric acid, 0.02 parts by mass of magnesium acetate, 0.01 parts by mass of lithium acetate, and 0.01 parts by mass of diantimony trioxide were added, and the mixture was subsequently heated to 290° C. under reduced pressure to carry out a polycondensation reaction, thereby obtaining virgin polyester resin A that was substantially free of particles.
[0073] (Virgin polyester resin B, C) The same additives as in virgin polyester resin A were added, polymerization was carried out in the same manner, and the final torque of the stirrer used to determine the completion of polymerization was changed to obtain virgin polyester resins B and C which essentially contained no particles.
[0074] (Virgin polyester resin D, E) Silicone resin (weight average molecular weight 40000, R2SiO 1.0 :RSiO 1.5 The silicone resin had a molar ratio of 1:4, and the hydrocarbon group R in the silicone resin had a molar ratio of phenyl groups and methyl groups of 60:40) added to virgin polyester resin B using a vented twin-screw kneader to obtain virgin polyester resin D which contains 5 ppm of silicon elemental water relative to the total mass of the polyester resin and is substantially free of particles, and virgin polyester resin E which contains 300 ppm of silicon elemental water and is substantially free of particles.
[0075] (Virgin polyester resin F) Before adding the metal compound when producing virgin polyester resin B, calcium carbonate having a volume average particle size of 1.1 μm was added so that the amount was 1.0 mass % relative to the polyester resin, and then polymerization was carried out in the same manner as for virgin polyester resin B to obtain virgin polyester resin F containing calcium carbonate.
[0076] (Virgin polyester resin G) Before adding the metal compound when producing virgin polyester resin B, alumina having a volume average particle size of 0.03 μm was added so that the amount was 1.5 mass % relative to the polyester resin, and then polymerization was carried out in the same manner as for virgin polyester resin B to obtain alumina-containing virgin polyester resin G.
[0077] (Virgin polyester resin H, I) Before adding the metal compound when producing virgin polyester resin B, wet silica having a volume average particle size of 2.6 μm after aggregation was added so that the amount was 2.0 mass% relative to the polyester resin, and then polymerization was performed in the same manner as for virgin polyester resin B to obtain silica-containing virgin polyester resin H. Similarly, wet silica having a volume average particle size of 1.4 μm after aggregation was added so that the amount was 1.0 mass% relative to the polyester resin, and then polymerization was performed in the same manner as for virgin polyester resin B to obtain silica-containing virgin polyester resin I.
[0078] (Virgin polyester resin J) An aqueous slurry of divinylbenzene / styrene copolymer crosslinked particles consisting of 80 mass % divinylbenzene, 15 mass % ethylvinylbenzene, and 5 mass % styrene and having a volume average particle size of 0.3 μm, obtained by the seed method for adsorbing monomers, was incorporated into virgin polyester resin D using a vented twin-screw kneader to obtain virgin polyester resin J containing 2.0 mass % divinylbenzene / styrene copolymer crosslinked particles relative to the polyester resin.
[0079] (Virgin polyester resin K) 68 parts by mass of terephthalic acid, 17 parts by mass of dimethyl cyclohexanedicarboxylate, 64 parts by mass of ethylene glycol, 20 parts by mass of spiroglycol, 0.06 parts by mass of manganese acetate, and 0.01 parts by mass of potassium hydroxide were dissolved at 150 ° C and stirred. After stirring, the temperature was raised to 235 ° C to distill off methanol, and then an ethylene glycol solution containing 0.02 parts by mass of triethyl phosphonoacetate was added to terminate the transesterification reaction. After stirring, a citric acid chelate titanium compound was added so that the titanium element was 5 ppm. After stirring again, the mixture was heated to 285 ° C under reduced pressure and the temperature was raised to perform a polycondensation reaction, and a virgin polyester resin K that does not substantially contain particles was obtained.
[0080] (Recycled polyester resin A) After producing a film having the following formulation, the film was recovered, compressed in a granulator, cut, and pelletized into cylindrical pellets having a diameter of 5 mm and a length of 20 mm, which was used as recovered polyester resin A. The ratios described below are expressed as mass ratios relative to the mass of the entire film. Virgin polyester resin B: 97.9% by mass Virgin polyester resin F: 1.9% by mass Virgin polyester resin G: 0.2 mass%.
[0081] (Recycled polyester resin B) After a film was produced using only the recovered polyester resin A as a raw material, the film was recovered, melt-kneaded in an extruder, and filtered to remove coarse particles and foreign matter using a filter with 5 μm openings. The film was then discharged from a die in the form of strands, and cut into chips while cooling to obtain recovered polyester resin B.
[0082] (Recycled polyester resin A) An intermediate roll was obtained by winding a film having the following composition. The ratios shown below are expressed as mass ratios relative to the mass of the entire film. Virgin polyester resin B: 89.7% by mass Virgin polyester resin J: 5.5% by mass Virgin polyester resin F: 4.8% by mass.
[0083] Next, a coating solution containing a crosslinking primer layer (manufactured by Dow Corning Toray Co., Ltd. under the trade name BY24-846) adjusted to a solid content of 1% by mass was applied to one side of the film unwound from the intermediate roll using a bar coater so that the coating thickness after drying would be 0.5 μm, and the coating was dried and cured at 120 ° C for 1 minute. Within 1 hour, a coating solution containing 100 parts by mass of an addition reaction type silicone resin (manufactured by Dow Corning Toray Co., Ltd. under the trade name LTC750A) and 2 parts by mass of a platinum catalyst (manufactured by Dow Corning Toray Co., Ltd. under the trade name SRX212) adjusted to a solid content of 5% by mass was applied to the film using a bar coater so that the coating thickness after drying would be 0.5 μm, and the film was dried and cured at 120 ° C for 1 minute, after which it was wound up to obtain a release film roll. The silicon element content of the prepared release film was measured and found to be 700 ppm.
[0084] Glass beads with a number-average particle size of 2 mm were added to 100 parts by mass of barium titanate (manufactured by Fuji Titanium Industries Co., Ltd. under the trade name of HPBT-1), 10 parts by mass of polyvinyl butyral (manufactured by Sekisui Chemical Co., Ltd. under the trade name of BL-1), 5 parts by mass of dibutyl phthalate, and 60 parts by mass of toluene-ethanol (mass ratio 30:30), and the mixture was mixed and dispersed for 20 hours using a jet mill, and then filtered to prepare a paste-like ceramic slurry. The obtained ceramic slurry was applied to a release film with a die coater so that the thickness after drying was 1 μm, and then dried and wound up to obtain a green sheet. The green sheet was then adsorbed and peeled off from the obtained laminate to obtain a used film roll.
[0085] The used film was cut with a crusher with a screen diameter of Φ5 mm, and then the cut used film was added to a washing tank equipped with an agitator blade, and 4.0% by mass of sodium hydroxide aqueous solution was added so that the washing concentration was 10% by mass. Furthermore, 0.02% by mass of polyoxyethylene octylphenyl ether was added to the sodium hydroxide aqueous solution added. The washing tank was heated to 85°C, and the mixture was washed for 20 minutes while stirring at a stirrer rotation speed of 200 rpm, and then washed with pure water. The polyester support material was further vacuum dried at 120°C, melt-kneaded in an extruder, and coarse particles and foreign matter were filtered out with a filter having a 5 μm opening, and then discharged from a die in the form of strands, cut while cooling, and made into chips, which was used as recycled polyester resin A.
[0086] (Recycled polyester resin B) Recycled polyester resin B was obtained in the same manner as for recycled polyester resin A, except that the sodium hydroxide concentration in the washing liquid was changed to 1.0 mass %.
[0087] (Recycled polyester resin C) An intermediate roll was obtained by winding up a film made only from virgin polyester resin A. Next, an aqueous solution containing 100 parts by mass of polyester resin (manufactured by GOO Chemical Industry Co., Ltd. under the trade name of Z836), 50 parts by mass of a melamine-based crosslinking agent (manufactured by Sanwa Chemical Co., Ltd. under the trade name of MW12LF), and 3 parts by mass of a fluorine-based surfactant (manufactured by GOO Chemical Industry Co., Ltd. under the trade name of RY2) adjusted so that the solid content of the polyester resin was 5% by mass was applied to one side of the film unwound from the intermediate roll using a bar coater so that the coating thickness after drying was 0.1 μm, and the film was dried and cured at 120° C. for 1 minute, followed by winding up to obtain an optical film roll.
[0088] Thereafter, the process from pulverization to chipping was carried out in the same manner as for Recycled Polyester Resin A, to obtain Recycled Polyester Resin C.
[0089] The properties of recycled polyester resin C showed that it had a lower shear viscosity despite having a higher IV than virgin polyester resin B. This is thought to be because the fluorosurfactant contained in the coating is persistent and chemically stable due to the bond between carbon and fluorine, which has a strong electro-negative effect, and because the residue of the fluorine compound contained in the polyester resin after cleaning acts like a mold release agent, just like silicone compounds.
[0090] (Recycled polyester resin D) After washing out the remaining beverage and other foreign matter from the PET beverage bottle, the bottle was crushed in a crusher to obtain flakes. The obtained flakes were washed with 3.5% by mass of sodium hydroxide aqueous solution at a washing concentration of 10% by mass, 85°C, and 30 minutes while stirring. After the alkali washing, the flakes were taken out and washed with distilled water at a washing concentration of 10% by mass, 25°C, and 20 minutes while stirring. The distilled water was replaced and washing was repeated two more times. After drying the flakes, they were melted in an extruder, and the finer foreign matter was filtered out twice more by changing the filter to one with a finer mesh size, and the third time was filtered out with a filter with the smallest mesh size of 5 μm to obtain recycled polyester resin D.
[0091] [Polyester resin blend] The method of compounding the polyester resin used in the production of the polyester film in the examples will be described. For a film with one layer, the layer is A, for a film with two layers, the layer is A and the layer is B, and for a film with three layers, the layers are A, B and C from the surface. The polyester resins supplied to the layers A, B and C were compounded at their respective compounding ratios to obtain a polyester film. The number of layers of the polyester film, the thickness of each layer, and the mass ratio (unit: mass%) of the polyester resin constituting each layer are shown in the table. The thickness of each layer is a value calculated from a calibration curve obtained by plotting the thickness of the film when the amount of resin discharged is increased or decreased for only one layer alone.
[0092] [Production of polyester film] Example 1 The polyester film had a three-layer structure consisting of layers A, B, and C, and the polyester resin in layer C was the same as that in layer A. The polyester resins fed to the extruders for layers A and B were mixed in the following ratios. The ratios listed below are mass ratios (unit: mass%) relative to the polyester resin that constitutes each layer. A layer, C layer: Recycled polyester resin A: 74% by mass Virgin polyester resin F: 23% by mass Virgin polyester resin G: 3% by mass B layer: Recycled polyester resin A: 60% by mass Recycled polyester resin A: 40% by mass.
[0093] The raw materials prepared for each layer were mixed in a blender, and then the raw materials for layers A and C were dried under reduced pressure at 160°C for 8 hours and fed to the single-screw extruder for layers A and C. The raw materials for layer B were dried under reduced pressure at 160°C for 8 hours and fed to the tandem extruder for layer B. The materials were melt-extruded at 280°C and filtered through a high-precision filter that captures more than 95% of foreign matter of 5μm or more, and then the polyester resins fed from one extruder that serves as both layers A and C were joined and laminated in a three-layer joining block that is laminated on both surface layers of the film, forming a three-layer laminate consisting of layers A, B, and C. After that, the material was passed through a T-die maintained at 280°C, and wrapped around a casting drum with a surface temperature of 25°C using a pinning device, and cooled and solidified to obtain an unstretched laminated film.
[0094] This unstretched film was preheated to 90°C using a preheating roll, and then heated from above and below using a radiation heater to 110°C while being stretched 3.3 times in the longitudinal direction by utilizing the difference in peripheral speed between the rolls. It was then cooled to 25°C using a cooling roll to produce a uniaxially stretched film.
[0095] Next, the uniaxially stretched film was held with a clip and preheated with 100 ° C. hot air in an oven, and then continuously stretched 4.0 times in the width direction while being heated with 120 ° C. hot air in the stretching process. The obtained biaxially stretched film was introduced into a heat treatment process and heat-treated with 235 ° C. hot air. The film that had undergone the heat treatment process was cooled from 235 ° C. to 135 ° C. while being subjected to a 7% relaxation treatment, and then cooled to 100 ° C. Next, the film was pulled out of the oven, and after removing both ends in the width direction, it was wound up to obtain an intermediate roll (polyester film) with a thickness of 25 μm. The obtained intermediate roll was slit to a width of 0.5 m while being rewound, and three product rolls were obtained. The properties of the obtained polyester film are shown in the table. It was a polyester film characterized by low shear viscosity, low coefficient of variation of surface thickness, and no foreign matter.
[0096] (Examples 2 to 5, Comparative Examples 3 and 5) The same procedure as in Example 1 was repeated except that the layer thickness and the blended resin of each layer were changed, and the results are shown in Table 1. In addition, in Comparative Examples 3 and 5, the melt extrusion temperature of the extruders for layers A, C, and B was changed to 310°C, resulting in an IV lower than 0.55, poor thickness uniformity, and gel-like foreign matter.
[0097] Example 6 The layer thickness and the blended resin of each layer were changed from Example 1. In addition, the raw materials prepared for layer C were stirred in a blender, then melt-extruded at 280°C in a vented twin-screw extruder for layer C, filtered through a high-precision filter that captures 95% or more of foreign matter of 3 μm or more, and then merged and laminated in a short heterogeneous three-layer merging block to form a three-layer laminate consisting of layers A, B, and C. Except for this, the same procedure as in Example 1 was carried out, and the results obtained are shown in Table 1.
[0098] (Examples 7 and 8) The layer structure was changed to only Layer A from Example 1, and the thickness and blended resin of Layer A were changed. In addition, this unstretched film was preheated to 120°C with a preheating roll, and then heated to 130°C from above and below using a radiation heater, stretched 5.4 times in the longitudinal direction by utilizing the difference in peripheral speed between the rolls, and subsequently cooled to 25°C with a cooling roll to obtain a uniaxially stretched film.
[0099] Next, the uniaxially stretched film was held with a clip and preheated in an oven with hot air at 105°C, and then continuously stretched 4.1 times in the width direction while being heated with hot air at 110°C in the stretching process. The obtained biaxially stretched film was introduced into a heat treatment process and heat-treated with hot air at 220°C. The film that had undergone the heat treatment process was subjected to a 2.6% relaxation treatment while being cooled from 220°C to 120°C, and then cooled to 100°C. Next, the film was pulled out of the oven, both ends in the width direction were removed, and then wound up to obtain an intermediate roll (polyester film). The obtained results are shown in the table.
[0100] (Examples 9 and 10) The layer structure was changed to only Layer A from Example 1, and the thickness and blended resin of Layer A were changed. In addition, this unstretched film was preheated to 90°C with a preheating roll, and then stretched 3.2 times in the longitudinal direction by utilizing the difference in peripheral speed between the rolls while heating to 110°C from above and below using a radiation heater, and subsequently cooled to 25°C with a cooling roll to obtain a uniaxially stretched film.
[0101] Next, the uniaxially stretched film was held with a clip and preheated in an oven with hot air at 105°C, and then continuously stretched 3.7 times in the width direction while being heated with hot air at 110°C in the stretching process. The obtained biaxially stretched film was introduced into a heat treatment process and heat-treated with hot air at 230°C. The film that had undergone the heat treatment process was subjected to a 5.5% relaxation treatment while being cooled from 230°C to 150°C, and then cooled to 100°C. Next, the film was pulled out of the oven, both ends in the width direction were removed, and then wound up to obtain an intermediate roll (polyester film). The results obtained are shown in the table.
[0102] Example 11 The layer structure was changed to only Layer A from Example 1, and the thickness and blended resin of Layer A were changed. In addition, this unstretched film was preheated to 90°C with a preheating roll, and then heated to 120°C from above and below using a radiation heater, stretched 2.7 times in the longitudinal direction by utilizing the difference in peripheral speed between the rolls, and subsequently cooled to 25°C with a cooling roll to obtain a uniaxially stretched film.
[0103] Next, the uniaxially stretched film was held with a clip and preheated in an oven with hot air at 140°C, and then continuously stretched 3.2 times in the width direction while being heated with hot air at 150°C in the stretching process. The obtained biaxially stretched film was introduced into a heat treatment process and heat-treated with hot air at 225°C. The film that had undergone the heat treatment process was subjected to a 2.0% relaxation treatment while being cooled from 225°C to 150°C, and then cooled to 100°C. Next, the film was pulled out of the oven, both ends in the width direction were removed, and then wound up to obtain an intermediate roll (polyester film). The results obtained are shown in the table.
[0104] (Comparative Examples 1, 2, and 4) The layer structure was changed to only Layer A from Example 1, and the thickness and blended resin of Layer A were changed. In addition, this unstretched film was preheated to 85°C with a preheating roll, and then heated to 120°C from above and below using a radiation heater, stretched 3.1 times in the longitudinal direction by utilizing the difference in peripheral speed between the rolls, and subsequently cooled to 25°C with a cooling roll to obtain a uniaxially stretched film.
[0105] Next, the uniaxially stretched film was held with a clip and preheated in an oven with hot air at 130°C, and then continuously stretched in the width direction by 4.0 times while being heated with hot air at 135°C in the stretching process. The obtained biaxially stretched film was introduced into a heat treatment process and heat-treated with hot air at 240°C. The film that had undergone the heat treatment process was cooled from 240°C to 110°C while being subjected to a 3.9% relaxation treatment, and then cooled to 70°C. Next, the film was pulled out of the oven, and after removing both ends in the width direction, it was wound up to obtain an intermediate roll (polyester film). The obtained results are shown in the table. In Comparative Example 1, the shear viscosity was higher than 220 Pa·s, and in Comparative Examples 2 and 4, the IV of the film was higher than 0.65, resulting in poor thickness unevenness. In addition, the silicon element content of the film obtained in Comparative Example 2 was 120 ppm, and as a result of SEM-EDX analysis of a foreign matter sample of the film, the inclusion of silicon element was confirmed in the foreign matter. In Comparative Example 4, gel-like foreign matter was found.
[0106] [Table 1]
[0107] [Table 2]
[0108] [Table 3]
[0109] [Table 4]
[0110] [Table 5]
[0111] [Table 6]
[0112] [Table 7] [Industrial Applicability]
[0113] The biaxially oriented polyester film of the present invention is suitable for optical or mold release applications because it has good thickness uniformity and little foreign matter. It is particularly suitable for optical applications, laminated ceramic capacitor mold release applications, or for the manufacture of all-solid-state battery materials. Examples of all-solid-state battery materials include solid electrolytes, positive electrodes, and negative electrodes.
Claims
1. A polyester recycled film having an intrinsic viscosity IV of 0.55 dl / g or more and 0.65 dl / g or less, and a shear viscosity ηH (Pa·s) at 280° C. and a shear rate of 31.4 rad / s of 50 Pa·s or more and 220 Pa·s or less.
2. 2. The polyester recycled film according to claim 1, wherein the shear viscosity ηH (Pa·s) and the intrinsic viscosity IV (dl / g) of the polyester film satisfy the following formula (A): 5×IV-1.04≦log(ηH)≦5×IV-0.92...Formula (A)
3. 2. The recycled polyester film according to claim 1, wherein the ratio ηH / ηL of the high-speed shear viscosity ηH to the low-speed shear viscosity ηL is 0.90 or more and 1.00 or less. However, the measurement temperature was 280° C., the high speed was 31.4 rad / s, and the low speed was 0.314 rad / s.
4. 2. The polyester recycled film according to claim 1, wherein both a high-speed shear viscosity ηH and a low-speed shear viscosity ηL are 70 Pa·s or more and 170 Pa·s or less. However, the measurement temperature was 280° C., the high speed was 31.4 rad / s, and the low speed was 0.314 rad / s.
5. 2. The polyester recycled film according to claim 1, wherein the film width is 400 mm or more, and the in-plane variation coefficient of the surface thickness measured continuously over a length of 1000 m in the longitudinal direction of the film is 0.8% or less.
6. 2. The polyester recycled film according to claim 1, having a thickness of 2 μm or more and 500 μm or less.
7. 2. The polyester recycled film according to claim 1, wherein the particle content is 0.3% by mass or less.
8. A polyester recycled film as described in claim 1, wherein the thickest layer contains 25 to 100 parts by mass of recovered or recycled polyester resin.
9. The polyester recycled film according to any one of claims 1 to 8, which is used for optical purposes, for release of multilayer ceramic capacitors, or for producing materials for all-solid-state batteries.
Citation Information
Patent Citations
Melt viscosity depressant for polyester resin and polyester resin composition containing the same
JP1995292226A
Biaxially oriented polyester film
JP2003082199A
Polyester film and method of manufacturing the same, backsheet for solar cell, and solar cell module
JP2012056090A
Polyester film
JP2014080593A
Polyester film
JP2014080594A
Cited By
Recycled polyester film and metallized film
JP2026091810A
Recycled polyester film and metallized film
JP2026091811A